Três arquitectas. Três gerações. Uma escola - Natascha Teixeira Cabral (2017)
This master thesis, Três Arquitectas. Três Gerações. Uma Escola, proposes a reflection and analysis through women's path in architecture, particularly regarding the national panorama and the particular case of the «Oporto School». For a long period of time, women have been excluded or have been assigned secondary positions throughout history and through diverse social contexts. This is something, which only started to change henceforth the XVIII century, thanks to the gradual access on higher education and other significant social changes. Nevertheless, many years later, feminine contributions still seem underestimated. For this reason, this research initially explores the problem of an architecture seen as a majority masculine practice, where women and minorities appear only to possess a diminished and limited role. With this emerges the attempt to reformulate an architecture which includes the perspectives of female architects, displaying professional and educational experienced scenarios. As the main purpose one intends to present and analyse the curriculum and work of a small sample of Portuguese female architects, as an evidence of their existence and starting point for the debate of their works vitality, or the lack of it, the reasons for their invisibility and the value of their contributions on diverse levels in which they occur. The choice fell particularly upon the work of three Portuguese female architects, which attended the same school and shared the same cultural vocational training, in order to investigate in which ways their female paths designed and constructed themselves, during three distinct generations, going back to the very first one of the renewed School of Higher Education of Architecture of Oporto until the present day.